Rheumatology Informatics System for Effectiveness: A National Informatics‐Enabled Registry for Quality Improvement. Issue 12 (28th November 2016) - Yazdany, Jinoos; Bansback, Nick; Clowse, Megan; Collier, Deborah; Law, Karen; Liao, Katherine P.; Michaud, Kaleb; Morgan, Esi M.; Oates, James C.; Orozco, Catalina; Reimold, Andreas; Simard, Julia F.; et al.
Abstract : Objective: The Rheumatology Informatics System for Effectiveness (RISE) is a national electronic health record (EHR)–enabled registry. RISE passively collects data from EHRs of participating practices, provides advanced quality measurement and data analytic capacities, and fulfills national quality reporting requirements. Here we report the registry's architecture and initial data, and we demonstrate how RISE is being used to improve the quality of care. Methods: RISE is a certified Centers for Medicare and Medicaid Services Qualified Clinical Data Registry, allowing collection of data without individual patient informed consent. We analyzed data between October 1, 2014 and September 30, 2015 to characterize initial practices and patients captured in RISE. We also analyzed medication use among rheumatoid arthritis (RA) patients and performance on several quality measures. Results: Across 55 sites, 312 clinicians contributed data to RISE; 72% were in group practice, 21% in solo practice, and 7% were part of a larger health system. Sites contributed data on 239, 302 individuals. Among the subset with RA, 34.4% of patients were taking a biologic or targeted synthetic disease‐modifying antirheumatic drug (DMARD) at their last encounter, and 66.7% were receiving a nonbiologic DMARD. Examples of quality measures include that 55.2% had a disease activity score recorded, 53.6% a functional status score, and 91.0% were taking a DMARD in the last year. Conclusion: RISE provides critical infrastructure for improving the quality of care in rheumatology and is a unique data source to generate new knowledge. Data validation and mapping are ongoing and RISE is available to the research and clinical communities to advance rheumatology.